Dylematy w sferze zatrudnienia osób niepełnosprawnych - Szluz, Beata (Seminare. Poszukiwania naukowe, 2008)
After termination of extremly important for every young man stage of preparation for work, the moment comes to make choice and face up proffesional reality. Disabled people require particular help in finding and keeping employment. Considering their situation on the labour market, they are entitled to avail from various systems of support: those which create conditions aimed at in¬ducing employers to create new work positions and those which increase mobility and preparation of future employees. These kind of activities are to help young people join the current of normal social functioning. Taking into account difficulties that come into existance in this field, the present reflection was dedicated to the problems in the sphere of employment of disabled people.